Application of Lean Production/Construction to Reduce Waste in Pipe Gas Construction (Case Study of Semare-Tie in KM 19 Pipa Porong Grati Gas Development Project PT Pertamina Gas) - Widayat, Taufik; Syairudin, Bambang (Institut Teknologi Sepuluh Nopember, 2019)
The lean approach, which was initially used in manufacturing industry, now is widely adopted by the construction industry called lean construction, in order to reduce waste and to optimize the value. This study was conducted to see the suitability of the lean construction approach on the EPC project of gas pipeline installation. This study is viewed from the Company side as the owner particularly in engineering aspect which is carried out by the company itself. Engineering work is deemed as a key to the next activity which is effective and efficient procurement and construction phase. Almost all similar projects show the same symptoms such as: low quality of engineering work (amendment value above 10%), target and realization lagging of its progress, re-work, weak coordination and residual materials. Therefore, the urgency to make improvements occur with the Lean Construction approach described in Big Picture Mapping, Value Stream Analysis Tool, Pareto Diagram, Fishbone Diagram at each stage of the engineering work EPC gas pipeline. Value Added (VA) activities were obtained at 39.35% and Non-Added Value (NVA) activities at 60.65%, engineering work quality classified as poor (amendment value 12.81%). The application of a lean construction approach is suitable to be applied in Company for gas pipe installation projects but with some notes. Then a comprehensive evaluation is required to evaluate man power, load, and skills needed and eventually to be standardized in an acknowledged company standard in order to make every project to be done punctually. The dominant root cause of the problem is the engineering contract form (a lump-sum engineering contract) and company policy as the reference to identify the contract form itself